Hegemony and Political Inequality: Elite Dominance through Gramsci and Marx - Muh. Firzah Rizki Putra Laksana; Joshua Alexandro Ferdinand; Aurera Damay Shafa Nayla Akbar; Maulidya Shavira; Vanesa Ivon Amalia; Farid Pribadi (Penerbit Goodwood, 2026)
Purpose: This study analyzes the persistence of elite political dominance in Indonesia, particularly through political dynasties, using Antonio Gramsci’s theory of hegemony and Karl Marx’s class analysis. Research Methodology: This research employs a qualitative approach using Critical Discourse Analysis (CDA). Data were collected through library research by examining academic literature and national media reports on political elites, corruption, and dynastic politics. Results: The findings reveal that elite dominance is systematically reproduced through the control of strategic political positions, economic resources, and ideological narratives. Although elections and formal democratic mechanisms continue to function, political competition remains unequal. Elite power operates not only through material control, as emphasized by Marx, but also through hegemonic processes that normalize dynastic rule as legitimate and natural in the public consciousness, consistent with Gramsci’s framework. Conclusions: Elite domination in Indonesia persists through the interaction of structural economic power and ideological hegemony. Democracy functions procedurally, but its substantive role in ensuring equality has been significantly weakened. Limitations: This study relied on secondary data and textual sources, limiting direct empirical observation. Contributions: This study integrates Marxian and Gramscian perspectives to provide a critical understanding of political inequality within contemporary democratic systems.